Konstruksi Fikih Kebangsaan Nahdlatul Ulama: Kajian terhadap Peran NU Perspektif Fiqh Siyasah - Muh. Sholihuddin; Saiful Jazil (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2021)
National jurisprudence is actually a response to the discourse on the relationship between religion and the State. Some Islamic groups who have the view of Islamic religious and political unity (al-Islam din wa daulah) that the three concepts are a complete and inseparable unity. The others said that the unity of religion and the State had ended when finally of al-Khulafa 'al-Rashidun. This matter when contextualized in Indonesia also becomes a long debate about the shape of the Indonesian state. Some want Islam to be the basis of the state and others want a nation-state. This is where national jurisprudence emerges as a way of looking at the relationship between religion and the State. Nahdlatul Ulama (NU) as an Islamic organization since the beginning of the emergence of the State has very strong national fiqh nuances. NU's acceptance of the nation-state as a form of State is evidence of this. With this manhaj fiqh siyasah, NU introduced the building of national political arguments without leaving Islamic teachings. Indonesia as a plural country is certainly the choice of the nation-state is the most ideal choice because it can minimize the potential for discrimination. Abstrak: Fikih kebangsaan merupakan respons atas wacana hubungan agama dan Negara. Sebagian kelompok memandang bahwa agama dan politik Islam (al-Islam din wa daulah) merupakan kesatuan yang utuh tak terpisahkan. Sebagian lain menyatakan bahwa kesatuan agama dan Negara itu sudah berakhir dengan selesainya al-Khulafa’ al-Rashidun. Dan ketika dikontekstualisasi di Indonesia menjadi perdebatan yang cukup panjang tentang bentuk Negara Indonesia. Sebagian menghendaki agar Islam menjadi dasar negara dan sebagian yang lain menghendaki nation-state. Di sinilah kemudian muncul fikih kebangsaan sebagai cara pandang dalam melihat hubungan agama dan Negara. Nahdlatul Ulama (NU) sebagai organisasi Islam sejak awal munculnya Negara sudah sangat kental nuansa fikih kebangsaannya. Penerimaan NU atas nation-state sebagai bentuk Negara menjadi bukti akan hal itu. Melalui manhaj fiqh siyasah ini, NU mengenalkan bangunan argumentasi politik kebangsaan tanpa meninggalkan ajaran Islam. Indonesia sebagai Negara yang plural tentu pilihan nation-state merupakan pilihan yang paling ideal karena dapat meminimalisasi potensi diskriminasi.